Ultrastructural aspects of acid phosphatase activity in Malpighian tubules of Triatoma infestans Klug - De Azeredo-Oliveira, Maria Tercília Vilela [UNESP]; Mello, Maria Luiza Silveira (My University, 1998)
Acid phosphatase activity was investigated ultrastructurally in Malpighian tubules of Triatoma infestans. Enzyme activity was demonstrated in laminated 'concretions' (distal cells) and in typical lysosomes, as well as in basal plasmalemma infoldings and basement membranes (especially in distal cells). This activity was assumed to be related to the excretory functions carried out mostly by the distal cells. Heterochromatin-nucleolus functional relationships involving RNA transcription may promote the nuclear reaction verified in the proximal cells and in some distal cells. A lead phosphate precipitate appeared free in the cytoplasm encircling the nuclei and was assumed to be a contamination from the nuclear precipitates.
Keywords: Acid phosphatases; Heterochromatin; Lysosomes; Malpighian tubules; Nucleolus; Triatoma infestans